Analysis of the Sociopetal-Sociofugal Architectural Conflict (SSAC) in High-Density Vernacular Sundanese Restaurants - Muhamad Sugeng Riyadi; James ED Rilatupa; Yophie Septiady (PT FORMOSA CENDEKIA GLOBAL, 2026)
Vernacular restaurant architecture in Indonesia increasingly deploys enclosed saung pavilions as spatial differentiators, yet the operational consequences of this design choice remain poorly understood. This study identifies the Sociopetal-Sociofugal Architectural Conflict (SSAC) a structural paradox in which the saung simultaneously creates intimate, comfortable conditions for dining guests while imposing navigational and communicational burdens on service staff. Grounded in Hall's Proxemics theory, Ching's architectural elements framework, and Bitner's Servicescape model, this research conducts qualitative field observation and behavioral mapping at Gurih 7 Restaurant in Bogor, Indonesia. The goal is to document and analyze how a single architectural typology produces opposing proxemic effects for two distinct user groups, and to establish the SSAC as a theoretically grounded phenomenon for recognition in future vernacular restaurant design and research.